Emil and the detectives - Smith, Rod 1947- (Penguin readers : level 3, 2006)
Emil is travelling alone to his grandmother's house in the city. He is carrying money to her from his mother. Then a man on the train streals the money. Emil follows the thief and an exciting adventure begins, with lots of detectives, a lift boy, and a fight in a bank! -- from p. 4 of cover